2022
DOI: 10.1109/access.2022.3154776
|View full text |Cite
|
Sign up to set email alerts
|

Personas for Artificial Intelligence (AI) an Open Source Toolbox

Abstract: Holzinger et al.: Personas for AI: An Open Source ToolboxThis article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…However, with the accelerated application of AI solutions and their limitations ("black boxes"), new approaches need to be considered and developed to account for these requirements. Notable contributions such as Personas for AI [66] demonstrate practical solutions in the domain of mental models and AI and are expected to receive further attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the accelerated application of AI solutions and their limitations ("black boxes"), new approaches need to be considered and developed to account for these requirements. Notable contributions such as Personas for AI [66] demonstrate practical solutions in the domain of mental models and AI and are expected to receive further attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compromise on the vast demand for AI while providing users with the best possible experience, the design of AI technologies and interfaces is crucial. Holzinger et al (2022) [187] showed the continuous changes in users' profiles and requirements. The use of AI technologies illustrated that some users might want to try new technologies, whereas others might not.…”
Section: Human-centered Designmentioning
confidence: 99%
“…To manage such variations, it is essential to have a centralized and predictive command and control system that can manage large and complicated data sets and continually learn through experience by optimizing the algorithm used to make predictions. Moreover, the human–AI interfaces gains some degree of human-like cognitive, self-executing, and self-adaptive capabilities and autonomy, and generating unexpected outputs that require non-deterministic interactions [ 11 ]. A good example is UCHealth in Colorado, which is a health system that delivers a high-quality patient care as well as a high-quality patient experience.…”
Section: Research Study Motivationmentioning
confidence: 99%
“…The toolbox contains guidelines and material supporting persona development for AI as well as templates and pictures for persona visualization. It is ready to use and freely available to the international research and development community [ 11 ]. Cognitive walkthrough (CW) is an efficient method that allows obtaining feedback on an innovative service at early stages, by walking some stakeholders through the new desired experience and asking them to comment.…”
Section: Research Study Motivationmentioning
confidence: 99%
See 1 more Smart Citation